Mechanistic Insights into Interactions at Urea−Hydroxyapatite Nanoparticle Interface - Fernando, Nimshi L.; Rathnayake, Dhanusha T.N.; Kottegoda, Nilwala; Jayanetti, J. K. D. S.; Karunaratne, Veranja; Jayasundara, Dilushan R. (ACS Publications, 2021)
Development of controlled release biomolecules by surface modification of hydroxyapatite nanoparticles has recently gained popularity in the areas of bionanotechnology and nanomedicine. However, optimization of these biomolecules for applications such as drug delivery, nutrient delivery requires a systematic understanding of binding mechanisms and interfacial kinetics at the molecular level between the nanomatrix and the active compound. In this research, urea is used as a model molecule to investigate its interactions with two morphologically different thin films of hydroxyapatite nanoparticles. These thin films were fabricated on quartz crystal piezoelectric sensors to selectively expose Ca2+ and PO4 3− sites of hydroxyapatite. Respective urea adsorption and desorption on both of these sites were monitored in situ and in real time in the phosphate buffer solution that mimics body fluids. The measured kinetic parameters, which corroborate structural predisposition for controlled release, show desorption rates that are one-tenth of the adsorption rates on both surfaces. Furthermore, the rate of desorption from the PO4 3− site is one-half the rate of desorption from the Ca2+ site. The Hill kinetic model was found to satisfactorily fit data, which explains cooperative binding between the hydroxyapatite nanoparticle thin film and urea. Fourier transform infrared spectra and X-ray photoemission spectra of the urea adsorbed on the above surfaces confirm the cooperative binding. It also elucidates the different binding mechanisms between urea and hydroxyapatite that contribute to the changes in the interfacial kinetics. These findings provide valuable information for structurally optimizing hydroxyapatite nanoparticle surfaces to control interfacial kinetics for applications in bionanotechnology and nanomedicine
Keywords: Hydroxyapatite nanoparticles; Piezoelectric sensors; Biomolecules; Nanomatrix; Nanomedicine